The carbon-to-oxygen ratio: implications for the spectra of hydrogen-dominated exoplanet atmospheres. Issue 1 (29th March 2019) - Drummond, Benjamin; Carter, Aarynn L; Hébrard, Eric; Mayne, Nathan J; Sing, David K; Evans, Thomas M; Goyal, Jayesh
Abstract: We present results from one-dimensional atmospheric simulations investigating the effect of varying the carbon-to-oxygen (C/O) ratio on the thermal structure, chemical composition, and transmission and emission spectra, for irradiated hydrogen-dominated atmospheres. We find that each of these properties of the atmosphere is strongly dependent on the individual abundances (relative to hydrogen) of carbon and oxygen. We confirm previous findings that different chemical equilibrium compositions result from sets of element abundances with the same C/O ratio but with different individual abundances of carbon and oxygen. We investigate the effect of this difference in composition on the thermal structure and simulated spectra. We also simulate observations using the PandExo tool and show that these differences are observationally significant with current (i.e. Hubble Space Telescope ) and future (i.e. James Webb Space Telescope ) instruments. We conclude that it is important to consider the full set of individual element abundances, with respect to hydrogen, rather than the ratios of only two elements, such as the C/O ratio, particularly when comparing model predictions with observed transmission and emission spectra.